NOTAS SOBRE EPIBIONTES E ECTOPARASITAS DE TARTARUGAS MARINHAS NA COSTA NORDESTE DO BRASIL - Alves, André Mota; Borges, João Carlos Gomes; Figueiredo, Larissa Mello; Alves, Rodolfo de França; de Jesus, João Victor; de Lima, Lucas Duarte; Soares, Michelle Evangelista; Lima, Victor Fernando Santana; Batista, Marcus Vinicius de Aragão (Archives of Veterinary Science, 2025)
The study focused on records of epibionts and ectoparasites of marine turtles on the northeastern coast of Brazil, specifically Chelonia mydas and Lepidochelys olivacea. A total of 117 Ozobranchidae leechs were identified, predominantly Ozobranchus branchiatus, with 6 specimens remaining classified as Ozobranchus sp. due to the absence of gill filaments for precise identification. Epibionts, comprising 14 specimens, included Chelonibia testudinaria, Platylepas hexastylos, and Lepas (Lepas) anatifera. The study also reported the first occurrence of Ozobranchus margoi as an ectoparasite of L. olivacea in Brazilian waters. The presence of these parasites, especially in turtles affected by fibropapillomatosis, raises concerns regarding their role as potential vectors of the associated herpesvirus (ChHV5). While O. branchiatus has been extensively documented, records of O. margoi in Brazilian waters are limited, highlighting the need for further research. Additionally, the study emphasizes the importance of standardized collection methods to ensure accurate parasite identification. The findings contribute to understanding the health threats faced by marine turtles and underscore the significance of ongoing conservation efforts.